Analysis of the Pop Up Market in Islamic Economics Business Perspective: Lesson Learned in Pekanbaru - Nurhadi Nurhadi (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
The market phenomenon in Pekanbaru in the last decade is enlivened by the existence of the pop-up market. By utilizing idle land around the settlement, the sellers provide goods for daily needs. This study is a mixed research model, which uses qualitative descriptive methods and direct observation. The research shows that the pop-up market just a momentary event that occurs when there is a crowd. It can be categorized as a traditional market with basic goods and carried out on mobile. According to a business economics perspective, the pop-up market plays an important role in fostering economic development, which leads to the welfare of society. Further, the existence of the pop-up market also in accordance with the principles of Islamic business economics which give attention to the micro and small enterprises due to the target of the pop-up market in Pekanbaru is the middle and lower classes. Keywords: Islamic Economics, Islamic Business, Pop Up Market